Presentation and outcomes of patients with clinically T1‐2, N0 oropharynx squamous cell carcinoma: The interplay of primary treatment modality and human papillomavirus status. Issue 1 (7th October 2022) - Al‐Qurayshi, Zaid; Zhu, Vivian L.; Bayon, Rodrigo; Buchakjian, Marisa R.
Abstract: Background: To examine the pattern of utilization and outcomes of definitive radiotherapy (RT) versus primary robotic‐assisted surgery in patients with early‐stage oropharyngeal squamous cell carcinoma (OPSCC). Methods: A retrospective cohort analysis of patients with clinically T1‐2, N0 OPSCC was performed using the National Cancer Database, 2010–2016. Results: A total of 1451 patients were included. Prevalence of human papillomavirus (HPV)‐positive tumors was 58.30%. Primary surgery was performed in 30.25% of the sample. Tongue base and clinically T1 tumors were each associated with a higher likelihood of undergoing surgery ( p  < 0.05). Histopathology of patients who underwent surgery demonstrated a prevalence of 15.95% with lymphovascular invasion, 16.67% with extranodal extension, 19.36% were T updated, and 30.00% were N upstaged. Improved survival was observed in the surgery + adjuvant RT group compared to RT alone for HPV‐positive tumors (HR: 0.27; 95%CI: 0.12, 0.62; p  = 0.002). Conclusion: This study provides epidemiological perspective regarding management pattern and outcomes of patients with early‐stage OPSCC.